Cosmic radiation dose measurements from the RaD‐X flight campaign. Issue 10 (28th October 2016) - Mertens, Christopher J.; Gronoff, Guillaume P.; Norman, Ryan B.; Hayes, Bryan M.; Lusby, Terry C.; Straume, Tore; Tobiska, W. Kent; Hands, Alex; Ryden, Keith; Benton, Eric; Wiley, Scott; Gersey, Brad; et al.
Abstract: The NASA Radiation Dosimetry Experiment (RaD‐X) stratospheric balloon flight mission obtained measurements for improving the understanding of cosmic radiation transport in the atmosphere and human exposure to this ionizing radiation field in the aircraft environment. The value of dosimetric measurements from the balloon platform is that they can be used to characterize cosmic ray primaries, the ultimate source of aviation radiation exposure. In addition, radiation detectors were flown to assess their potential application to long‐term, continuous monitoring of the aircraft radiation environment. The RaD‐X balloon was successfully launched from Fort Sumner, New Mexico (34.5°N, 104.2°W) on 25 September 2015. Over 18 h of flight data were obtained from each of the four different science instruments at altitudes above 20 km. The RaD‐X balloon flight was supplemented by contemporaneous aircraft measurements. Flight‐averaged dosimetric quantities are reported at seven altitudes to provide benchmark measurements for improving aviation radiation models. The altitude range of the flight data extends from commercial aircraft altitudes to above the Pfotzer maximum where the dosimetric quantities are influenced by cosmic ray primaries. The RaD‐X balloon flight observed an absence of the Pfotzer maximum in the measurements of dose equivalent rate. Key Points: The RaD‐X campaign provided dosimetric measurement at seven altitudes from 8 km to over 32 km Flight‐averaged absorbed dose rates measured by the TEPC, Liulin, and Teledyne detectors agree to within 15% in stratosphere The balloon flight data show the absence of a distinct Pfotzermaximum in the dose equivalent rate